2016
DOI: 10.1136/archdischild-2015-309586
|View full text |Cite
|
Sign up to set email alerts
|

Children and road traffic injuries: can't the world do better?

Abstract: Road traffic injuries (RTI) impose a substantial health burden among children. Globally, 186 300 children (under 18 years) die from RTI each year. It is the fourth leading cause of death among children aged 5-9 years, third among children aged 10-14 years and first among children aged 15-17 years. At the regional level, sub-Saharan Africa accounts for 35.2% of global child deaths caused by RTI; that number is still increasing. Male children are about two times more likely to die due to RTI than female children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 51 publications
(32 reference statements)
1
20
0
4
Order By: Relevance
“…Each year there are over 1 million deaths associated with RTAs and an estimated 20–50 million non-fatal road traffic injuries (RTIs) around the world ( 30 ). These RTAs result in the deaths of 186,300 children (ages 0–17 years) ( 31 ). Boys are twice as likely to be killed in RTAs as girls.…”
Section: Addressing Specific Causes Of Pediatric Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Each year there are over 1 million deaths associated with RTAs and an estimated 20–50 million non-fatal road traffic injuries (RTIs) around the world ( 30 ). These RTAs result in the deaths of 186,300 children (ages 0–17 years) ( 31 ). Boys are twice as likely to be killed in RTAs as girls.…”
Section: Addressing Specific Causes Of Pediatric Injurymentioning
confidence: 99%
“…LMICs account for approximately 95% of all children killed by RTAs, with the brunt of this burden borne by countries in Sub-Saharan Africa. Over 35% of global child deaths from RTAs are in Sub-Saharan Africa ( 31 ). To address this significant problem, several steps should be taken.…”
Section: Addressing Specific Causes Of Pediatric Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the symptoms included flashbacks of the event, anxiety, fear of re-injury and mood disorders. Most child road deaths occur in sub-Saharan Africa; Li et al (2016) found that in 1990, 18.8% of child road deaths had occurred in the region, with the proportion of deaths almost doubling to 35.2% by 2016. South Africa is one of the leading contributors to this public health concern.…”
Section: Introductionmentioning
confidence: 99%
“…A particular challenge in establishing data systems is the lack of human, technical and financial capacity; which may require international support to address particularly at the early stage of implementing plans for addressing the burden of child injuries in Ethiopia. A comprehensive package with a detailed roadmap will make it possible to reduce the burden of injuries and violence in Ethiopia [ 23 ]. As a starting point, we recommend adding child injuries prevention into the training of Ethiopia’s successful Health Extension Worker Program [ 24 ].…”
Section: Discussionmentioning
confidence: 99%